The effect of strain on the adsorption of CO on Pd(100) - Wu, M. W.; Metiu, H. (The Journal of chemical physics, 2000)
We study how the binding energy, the vibrational frequencies and the adsorption isotherm of CO on Pd(100) are modified when the solid is subject to uniform strain. The parameters controlling the thermodynamics of adsorption (the adsorption energy, the vibrational frequencies of the adsorbed molecules and the interaction energy between the molecules) have been calculated by using density functional theory. These parameters are then used in a grand canonical Monte Carlo simulation that determines the CO coverage when the surface is in thermodynamic equilibrium with a CO gas, at a specified pressure and temperature. We find that this is substantially affected by the strain. Our results, along with those obtained by others, suggest that the development of “elastochemistry,” a study of the change in the chemical properties of a surface when subjected to strain will lead to interesting and measurable results. It also suggests that differences in chemical activity between clusters on a support and clusters in gas phase may be partly due to the strain induced when a cluster is placed on the support.